PET/CT F18-FDG with soft tissue plasmacytomas in multiple myeloma - Alejandro Martí; Sarai Morón; Sandra Chinchilla; Eliana González (European Journal of Hybrid Imaging, 2021)
Abstract Multiple myeloma is characterized by malignant proliferation of clonal plasma cells. Usually, appears as a generalized disease but it can present as solitary bone plasmacytoma or a solitary soft tissue mass or extramedullary plasmacytoma. In the case of extramedullary involvement, it could present as soft tissue plasmacytomas and the prognosis is poor. The 18F-FDG PET/CT could be a valuable tool for characterization of the medullary and extramedullary involvement. We present a case of F18-FDG PET/CT with extramedullary involvement with soft tissue plasmacytomas in the setting of MM.